2019
DOI: 10.1007/s40266-019-00706-4
|View full text |Cite|
|
Sign up to set email alerts
|

Suitable Use of Injectable Agents to Overcome Hypoglycemia Risk, Barriers, and Clinical Inertia in Community-Dwelling Older Adults with Type 2 Diabetes Mellitus

Abstract: The management of type 2 diabetes mellitus in older adults requires a comprehensive understanding of the relationship between the disease (medical) and the functional, psychological/cognitive, and social geriatric domains, to individualize both glycemic targets and therapeutic approaches. Prevention of hypoglycemia is a major priority that should be addressed as soon as its presence or risk is detected, adjusting the target and therapeutics accordingly. Nonetheless, treatment intensification should not be negl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…Stigma was associated with severed relationships; social isolation; reduced work opportunities; and distress, depression, anxiety, and lowered self-esteem, self-worth, and patient self-efficacy [ 37 , 41 , 81 , 88 , 89 , 91 , 100 ]. In patients with T2DM, the perceived stigma was related to their experience of insulin self-injection [ 37 , 76 , 79 , 101 ]; in patients with COPD, the internalised stigma was evident when they described their disease as “self-inflicted” [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Stigma was associated with severed relationships; social isolation; reduced work opportunities; and distress, depression, anxiety, and lowered self-esteem, self-worth, and patient self-efficacy [ 37 , 41 , 81 , 88 , 89 , 91 , 100 ]. In patients with T2DM, the perceived stigma was related to their experience of insulin self-injection [ 37 , 76 , 79 , 101 ]; in patients with COPD, the internalised stigma was evident when they described their disease as “self-inflicted” [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Within healthcare research the concept of clinical inertia, i.e. the recognition of the medical problem between a patient and a physician, but with failure to act upon this (Phillips et al, 2001 ; Valencia, Florez, & Palacio, 2019 ), has been shown to have negative health consequences (e.g. delayed treatment, Valencia et al, 2019 ).…”
Section: Motivations To Provide Carementioning
confidence: 99%
“…the recognition of the medical problem between a patient and a physician, but with failure to act upon this (Phillips et al, 2001 ; Valencia, Florez, & Palacio, 2019 ), has been shown to have negative health consequences (e.g. delayed treatment, Valencia et al, 2019 ). It may be that a similar concept around inertia in caregiving may exist that prevents or delays caregivers in seeking necessary support when motivations falter or when care demands change.…”
Section: Motivations To Provide Carementioning
confidence: 99%
“…given the low risk of hypoglycemia, the weight loss benefit, the potential benefits in comorbidities and the weekly administration [9]. Its use must be accompanied by adapted nutritional therapy, and appropriate physical activity recommendations (aerobic and resistance training) to avoid the loss of muscle mass, including strength, flexibility and balance exercises [10].…”
mentioning
confidence: 99%